PREDIKSI PERILAKU RAMAH LINGKUNGAN YANG DIPENGARUHI OLEH NILAI DAN GAYA HIDUP KONSUMEN - Ali, Suprihatin (JURNAL PERSPEKTIF BISNIS, 2013)
The research objective is to investigate the effect of value and lifestyle on consumerâs environmental behaviour. This study use convenience sampling technique to collect 433 respondents in Bandar Lampung. Results support the hypothesis. The research reveals that value and lifestyle can influence significantly toward consumerâs environmental behaviour. Â Keyword: Environmental value, lifestyles and green behaviour